2013
DOI: 10.1007/s11064-013-1054-8
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Exposure to Methylmercury in Wildtype and pdr-1/parkin Knockout C. elegans

Abstract: We examined the impact of early-life exposure to methylmercury (MeHg) on Caenorhabditis elegans (C. elegans) pdr-1 mutants, addressing gene-environment interactions. We tested the hypothesis that early-life exposure to MeHg and knockout (KO) of pdr-1 (mammalian: parkin/PARK2) exacerbates MeHg toxicity and damage to the dopaminergic (DAergic) system. pdr-1KO worms showed increased lethality and decreased lifespan following MeHg exposure. Mercury (Hg) content, measured with Inductively Coupled Plasma-Mass Spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
2
21
1
Order By: Relevance
“…These mutants have an impaired DA biosynthesis and, likewise, the corresponding chromatogram lacks a clear DA signal. In fact, homogenates of cat-2 worms are not completely free of DA [33]. However, determined concentrations in our studies were between the LOD and LOQ.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…These mutants have an impaired DA biosynthesis and, likewise, the corresponding chromatogram lacks a clear DA signal. In fact, homogenates of cat-2 worms are not completely free of DA [33]. However, determined concentrations in our studies were between the LOD and LOQ.…”
Section: Resultsmentioning
confidence: 57%
“…After a five-minute acclimation period, the locomotion rate was assessed as the number of body-bends per 20 s, and data are presented as the change in body bends (body bends on food – body bends off food); analysis was carried out after coding of plates. Worms deficient in cat-2 were used as positive control since they are TH-deficient [33]. …”
Section: Methodsmentioning
confidence: 99%
“…Studies in Caenorhabditis elegans conducted by Martinez-Finley and colleagues have shown a latency period for neurodegeneration in combination with susceptibility of genetic background [41, 42]. The first study described the impact of early-life exposure to MeHg and knockdown of skn - 1 , the major stress-activated cytoprotective transcription factor, on dopaminergic (DAergic) neurodegeneration, mercury content, and stress reactivity in the nematode C. elegans .…”
Section: Contribution Of Genetics To Methylmercury Toxicitymentioning
confidence: 99%
“…Dopamine-dependent behavioral analysis revealed an effect of MeHg on N2 wild-type worms, but no effect on pdr - 1 KO worms. These results suggested that pdr - 1 KO worms were more sensitive to MeHg than wild-type worms, but MeHg did not exacerbate behavioral changes already present in pdr-1KOs, even after a period of latency [42]. …”
Section: Contribution Of Genetics To Methylmercury Toxicitymentioning
confidence: 99%
“…Non-mammalian models that are used to study toxicity such as C. elegans (Martinez-Finley et al [25]) and Zebrafish (Danio rerio) (Carvalho et al [26]) are becoming more commonly used to study mechanisms of toxicity and as alternatives to mammalian animal testing. Some advantages of using zebrafish embryos (ZFEs) in toxicity assessment include: a transparent "shell" or chorion that encloses the developing ZFEs during early development; embryos whose tissues also are transparent early in development; rapid ex utero development; and the ability to directly and accurately deliver chemicals of interest to developing ZFEs [27][28][29].…”
Section: Introductionmentioning
confidence: 99%